2000
DOI: 10.2136/sssaj2000.643999x
|View full text |Cite
|
Sign up to set email alerts
|

Timing Effects of Deep Tillage on Penetration Resistance and Wheat and Soybean Yield

Abstract: In many southeastern Coastal Plain soils, subsoil pans have strengths that restrict root growth. To reduce strengths, soils are deep tilled annually, and perhaps biannually for double cropping. We evaluated the effect of deep tillage in fall, in spring, or at both times on strength of a Goldsboro loamy sand (fine loamy, siliceous, thermic Aquic Kandiudult) and on the yield of wheat (Triticum aestivum L.) and drilled soybean [Glycine max (L.) Merr.] in a double‐cropped system. Treatments consisted of all combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1
12

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 14 publications
3
41
1
12
Order By: Relevance
“…Deep plowing with subsoiler has similar characteristics to that of the chisel plow, but the only difference is the plowing depth. Studies have shown that deep tillage system can improve soil physical properties including decreased bulk density, infiltration rate and hydraulic conductivity, increased soil moisture in soil profile and yield under dryland production (Busscher et al, 2000;Busscher et al, 2002;Busscher et al, 2006;Laddha and Totawat, 1997;Motavalli et al, 2003b;Nitant and Singh, 1995) . Conservation tillage is the recommended method which helps to retain the crop residues in the soil surface at the same time conserves the soil and water (Sow et al, 1997).…”
Section: Justification Of the Studymentioning
confidence: 99%
“…Deep plowing with subsoiler has similar characteristics to that of the chisel plow, but the only difference is the plowing depth. Studies have shown that deep tillage system can improve soil physical properties including decreased bulk density, infiltration rate and hydraulic conductivity, increased soil moisture in soil profile and yield under dryland production (Busscher et al, 2000;Busscher et al, 2002;Busscher et al, 2006;Laddha and Totawat, 1997;Motavalli et al, 2003b;Nitant and Singh, 1995) . Conservation tillage is the recommended method which helps to retain the crop residues in the soil surface at the same time conserves the soil and water (Sow et al, 1997).…”
Section: Justification Of the Studymentioning
confidence: 99%
“…Dentre os atributos físicos utilizados para avaliar a compactação do solo, a resistência do solo à penetração e a densidade do solo têm sido atualmente priorizadas para avaliar sistemas de uso e manejo, por serem atributos diretamente relacionados ao crescimento das plantas e de fácil e rápida determinação (BUSSCHER et al, 2000). Além, a resistência do solo à penetração apresenta maiores correlações com o crescimento radicular (STOLF, 1991), destacando-se como a melhor estimativa do impedimento mecânico ao crescimento radicular e como um indicador mais sensível à compactação do solo (SERAFIM et al, 2008).…”
Section: Introductionunclassified
“…Water infiltration, porosity, bulk density (D b ), and soil resistance to penetration (PR) are some of the physical attributes that are used to characterize soil compaction. Nowadays, PR is considered the most indicative attribute of soil compaction in management systems (Busscher et al, 2000;Beutler et al, 2001). This is because it is directly related to plant growth (Letey, 1985) and shows a strong relationship with plant root growth (Hoad et al, 2001).…”
Section: Introductionmentioning
confidence: 99%